Ride performance analysis of half-car model for semi-active system using RMS as performance criteria - Ihsan, Sany Izan; Ahmadian, Mehdi; Faris, Waleed Fekry; Blancard, E. D. (IOS Press, 2009)
The work aims to study the root mean square (RMS) responses to acceleration input for four state variables: the m_{s} vertical acceleration, the m_{s} pitch angular acceleration and the front and rear deflections of the suspensions. A half-car two degree-of-freedom model of semi-active control scheme is analyzed and compared with the conventional passive suspension system. Frequency response of the transfer function for the heave, pitch of the sprung mass and suspension deflections are initially compared and then mean square analysis is utilized to see the effect of semi-active scheme. Results indicate that significant improvements were achieved in the sprung mass heave and pitch responses using semi-active control scheme. However results for the rear and front suspension deflection show that there are limiting values of damping coefficient beyond which, the semi-active scheme becomes disadvantageous than the passive system.